Inventory Control Practices and Financial Performance of Robina Fresh Meats - Roque, Ryan C.; Guzman, Lovely Joy M. De (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to determine the effectiveness of inventory control practices and financial performance of Robina Fresh Meats. Descriptive method of research was used. Survey questionnaires were distributed to 200 employees related to inventory control. The inventory control practices of Robina Fresh Meats were assessed as very effective as to inventory count and label accuracy; and effective as to ordering and stock level determination, spoilage control, and inventory system. Financial performance was assessed as very satisfactory. Results showed a significant relationship between “ordering and stock level determination” and “sales growth” and between “inventory count and label accuracy, and inventory system” and “sales growth, inventory cost reduction and increase in net profit”. The researcher recommended to keep a balanced stock levels in outlet storage, avoid overstocking, do re-forecast for an additional order if needed, explore the existing inventory system, observe strict compliance with the inventory control and provide continuous training.